P250 Does Ethnicity Influence Patient's Preferences for Treatment Outcome? The Israeli Experience. (27th May 2021) - Broide, E; Richter, V; Mari, A; Khoury, T; Shirin, H; Naftali, T
Abstract: Background: IBD behaves differently among different ethnic groups. Patients perceptions and priorities for treatment outcome may well be influenced by their culture and beliefs. However, data on the impact of ethnicity on IBD patient's attitude and expectation for treatment outcomes are still scares. We aimed to compare patient's preferences and priorities for treatment outcomes among Jewish and Muslims IBD patients in Israel. Methods: A prospective survey was conducted among Muslims IBD patients and compared to historical data set of Jewish IBD patients. Data included demographics and socioeconomics parameters as well as clinical data. Patients were asked to rank ten items regarding their preferences for treatment outcome, based on the ten IBD disk items. Cluster analysis was used to classify both patient's groups into homogeneous subgroups according to their preferred IBD items. Results: 391 patients were included in our analysis; 121 Muslims patients were compared to historical data base of 240 Jewish patients, 67.9% CD patients and 33.5% UC patients. Both groups were similar regarding age, disease activity and treatment, but the duration of disease was longer in the Jewish population (a median of 9 vs 6 years, p=0.01). As a group, Muslim patients ranked the priorities for treatment outcome lower compared to the Jewish population. The items with the highest priority were the same in both groups with abdominal pain, energy, and regular defecation ranking highest. There were no differences between Muslims men and women, but the Jewish women attached higher priority to abdominal pain, energy, sleep, joint pain, education and work. The cluster with the higher scores was characterized by more females (p<0.001), Jews (p<0.001), urban residency (p<0.001), working hours per week (p=0.003), lower income (p= 0.011) CD patients (p=0.011), active disease (p<0.001), and lower response to treatment (p=0.002). Multivariable regression analysis revealed an association between higher patient's ranking and Jewish religion (OR 4.77) male gender (OR 0.5), income level (OR 0.2), active disease (OR 5.29) and CD (OR 0.4). Conclusion: The ethnic difference has a high impact on patient's ranking of priorities for treatment outcome. These differences can be explained by socioeconomic factors. Despite the ethnic and cultural differences, symptoms relief is in the highest priority in both patient groups.